Blunt Facial Trauma Causing Isolated Optic Nerve Hematoma. (21st January 2013) - Parab, R.; Fung, C. I.; Van Der Merwe, Gerrit
Abstract : Traumatic optic neuropathy is an uncommon, yet serious, result of facial trauma. The authors present a novel case of a 59-year-old gentleman who presented with an isolated blunt traumatic left optic nerve hematoma causing vision loss. There were no other injuries or fractures to report. This case highlights the importance of early recognition of this rare injury and reviews the current literature and management of traumatic optic neuropathy.